2021
DOI: 10.1016/j.ajpath.2021.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Regulation of Alveolar Type 2 Cell and Fibroblast Apoptosis by Plasminogen Activator Inhibitor 1 in Lung Fibrosis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…A growing body of evidence demonstrates that IPF fibroblasts are resistant to apoptosis [7][8][9][10]. The mechanisms are unclear, but evidence indicates the participation of the extrinsic pathway of apoptosis, such as the inhibition of Fas-mediated apoptotic cell death [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of evidence demonstrates that IPF fibroblasts are resistant to apoptosis [7][8][9][10]. The mechanisms are unclear, but evidence indicates the participation of the extrinsic pathway of apoptosis, such as the inhibition of Fas-mediated apoptotic cell death [8].…”
Section: Discussionmentioning
confidence: 99%
“…During physiological regeneration, fibroblasts are eliminated by apoptosis, and evasion or resistance to this process has been associated with progressive fibrosis. In this context, it has been reported that fibroblasts and myofibroblasts from patients with IPF are resistant to apoptosis, although the molecular mechanisms involved are uncertain [7][8][9][10]. Due to the central role that mitochondria play in the implementation, amplification, and regulation of cellular apoptosis, this organelle would be involved in the apoptosis resistance of IPF fibroblasts, but this has not yet been studied in depth.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we showed that the increased expression of plasminogen activator inhibitor 1 (PAI-1), a serine protease inhibitor playing a critical role in the development of lung fibrosis [24][25][26][27], contributes importantly to ATII cell senescence in the fibrotic lung [15,28]. We also showed that PAI-1 expression increases with age in mouse ATII cells [29] and that PAI-1 positively regulates p53 expression and promotes ATII cell senescence through activating the p53-p21-pRb cell cycle repression pathway, although the mechanism underlying PAI-1 induction of p53 remains to be determined [15]. As p53 is a master cell cycle repressor and PAI-1 expression is increased in many senescent cells [15,28,[30][31][32][33][34], uncovering the molecular mechanism by which PAI-1 regulates p53 expression will have a significant impact on multiple diseases.…”
Section: Introductionmentioning
confidence: 99%
“…For terminal patients, lung transplantation is often considered as a management strategy (4). Recent studies have suggested that small lipid molecules, such as fatty acids, cholesterol, arachidonic acid metabolites, and phospholipids, may play a signi cant role in the development of IPF (5)(6)(7)(8). However, the exact causal relationship between lipid metabolites and IPF is still not fully understood.…”
Section: Introductionmentioning
confidence: 99%